Application of energy dispersive X-ray analysis technique in chalcogenide metal thin films: Review - Ho, Soon Min (International Digital Organization for Scientific Information, 2016)
Thin films have been synthesized in the presence of different precursors using various deposition methods such as chemical bath deposition, electrodeposition and successive ionic layer adsorption and reaction. The obtained thin films could be investigated using energy dispersive X-ray (EDX) technique in terms of compositional characterization. Generally, EDX analyzer was equipped with the scanning electron microscopy as described by many researchers. In this work, the EDX analysis has been carried out in order to improved quality control and rapid identification of source.